2018
DOI: 10.1136/bmjopen-2017-020712
|View full text |Cite
|
Sign up to set email alerts
|

Who teaches medical billing? A national cross-sectional survey of Australian medical education stakeholders

Abstract: ImportanceBilling errors and healthcare fraud have been described by the WHO as ‘the last great unreduced health-care cost’. Estimates suggest that 7% of global health expenditure (US$487 billion) is wasted from this phenomenon. Irrespective of different payment models, challenges exist at the interface of medical billing and medical practice across the globe. Medical billing education has been cited as an effective preventative strategy, with targeted education saving $A250 million in Australia in 1 year from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…2 In Australia, despite an overarching assumption that doctors have high legal literacy in relation to correct billing using Australia's national universal health system, Medicare, 2 a recent study seeking to measure that experience, challenged that assumption, suggesting medical practitioners may instead be experiencing difficulties accessing reliable medical billing advice. 3 In 2016, the Government of the Netherlands acknowledged this educational gap by introducing a requirement that universities and medical specialist training colleges provide education to medical practitioners in relation to medical billing and the costs of providing care, the stated aim being to tackle billing mistakes and fraud through prevention, rather than solely through punitive post-payment policing. 4 However, while medical billing education has been recognised as an effective measure to improve compliance, reduce incorrect billing and improve integrity of health financing systems, 5 formal education initiatives remain rare and many medical practitioners may have received no training whatsoever.…”
Section: Introductionmentioning
confidence: 99%
“…2 In Australia, despite an overarching assumption that doctors have high legal literacy in relation to correct billing using Australia's national universal health system, Medicare, 2 a recent study seeking to measure that experience, challenged that assumption, suggesting medical practitioners may instead be experiencing difficulties accessing reliable medical billing advice. 3 In 2016, the Government of the Netherlands acknowledged this educational gap by introducing a requirement that universities and medical specialist training colleges provide education to medical practitioners in relation to medical billing and the costs of providing care, the stated aim being to tackle billing mistakes and fraud through prevention, rather than solely through punitive post-payment policing. 4 However, while medical billing education has been recognised as an effective measure to improve compliance, reduce incorrect billing and improve integrity of health financing systems, 5 formal education initiatives remain rare and many medical practitioners may have received no training whatsoever.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, how much non-compliant billing is deliberate is uncertain, as it rests in a spectrum with criminal fraud at one end and unintentional errors at the other and currently the precise quantum of each is unknown. 4 This is largely because the problem is not what can be seen, but what cannot. Lax regulation, government maladministration, system complexity and the fact that medical practitioners are never taught how to use the system correctly at any point in their careers have all been cited as factors contributing to this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Lax regulation, government maladministration, system complexity and the fact that medical practitioners are never taught how to use the system correctly at any point in their careers have all been cited as factors contributing to this problem. 4 Increasing complexity has occurred in tangent with increased penalties for non-compliance 5 and pressure on medical practitioners to bill correctly has reached the point where some authors have suggested that compliance with Medicare billing rules has become a contributing factor to medical practitioner burnout and suicide. 6 However, one area of activity that has been overlooked is improving user knowledge of the medical billing system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations